A Survey on Factors Influencing the Work–Family–Health Balance of an Interventional Radiologist - Haridass, Shoban; Kalva, Sanjeeva; Yadav, Bijesh; Keshava, Shyamkumar Nidugala (Indian Journal of Radiology and Imaging, 2023)
Aim: Burnout and stress-related health disorders are on the rise among physicians. The aim of this study is to report the results of a survey on factors affecting the work–life balance of interventional radiologists (IR).Material: The survey consisted of 30 questions focusing on work, family, and personal health. The questionnaire addressed knowledge, attitude, and practice. This online survey was sent to IRs across the globe and the responses were analyzed by three IRs (SH, SNK, SK).Results: On univariate analysis, the major risk factors for burnout were presence of weekend duties (n = 91, 98.9%, p = 0.02), absence of support group at workplace (n = 36, 39.1%, p = 0.005), having tough time with administration (n = 61, 66.3%, p = 0.001), not able to spend quality time on family (n = 30, 32.6%, p = 0.035), and inability to find time to do things that one enjoys (n = 53, 57.6%, p = 0.0002). However, multivariate analysis revealed that those having tough time with administration (odds ratio = 2.77 [95% confidence interval [CI]: 1.12–6.48], p = 0.02) and those who could not find time to do things one enjoys (odds ratio = 4.79 [95% CI: 1.42–16.1], p = 0.01) were only statistically significant.Conclusion: Burnout is common among IRs and is considered a significant issue that needs to be addressed. Teamwork, a support structure for major events, healthy lifestyle, and dedicated time for family may combat the burnout.
Keywords: interventional radiology; occupational burnout; stress; work-family-health